1979
DOI: 10.1002/jsfa.2740300308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and sulphur fertilisers on the yield, N and S content, and amino acid composition of the grain of spring wheat

Abstract: Spring wheat (cv. Kleiber) was grown in three pot experiments in a soil containing 10 mg kg-1 KH~P04-soluble sulphur with different rates of nitrogen and sulphur fertilisers. Without added S the yields of grain dry matter and crude protein were either unchanged (glasshouse experiment) or significantly decreased by the N treatments (controlled environment experiments). With added S the N fertiliser increased the yields by 4&110%. The experiments produced grain with a wide range of N and S contents, the latter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 36 publications
3
26
0
3
Order By: Relevance
“…Sulfur application has been reported to decrease (Byers and Bolton 1979) or increase (Archer 1974) grain nitrogen. The present experiments, over a wider range of sulfur supply levels, have shown (Tables 2 and 3) that an increment of applied sulfur may increase or decrease grain nitrogen or have no effect, depending on the sulfur status and the nitrogen supply.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sulfur application has been reported to decrease (Byers and Bolton 1979) or increase (Archer 1974) grain nitrogen. The present experiments, over a wider range of sulfur supply levels, have shown (Tables 2 and 3) that an increment of applied sulfur may increase or decrease grain nitrogen or have no effect, depending on the sulfur status and the nitrogen supply.…”
Section: Discussionmentioning
confidence: 98%
“…The wide (N/S), ratios of sulfur-sufficient samples represented in area B could be due to high nitrogen supply especially during grain filling or to an accumulation of nitrogen due to a limitation on yield by some other factor. Data from Archer (1974) and Byers and Bolton (1979) are also plotted. These represent a range of cultivars and culture conditions but embrace a limited number of sulfur treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between nitrogen and sulfur nutrition of the wheat crop also had an effect on grain amino acid composition. Byers and Bolton (1979) and Wrigley et al (1980) observed that high levels of nitrogen supply and marginal levels of sulfur supply resulted in marked reductions of the concentration of cysteine and methionine. Timms et al (1981) observed the similar reductions caused by a nitrogento-sulfur imbalance induced by late-season fertilization of wheat with urea.…”
Section: Wheatmentioning
confidence: 99%
“…An environmental policy leading to reduce SO 2 atmospheric emissions, the massive use of nitrogen and phosphorus fertilizers and the introduction of high yielding crop cultivars resulted in a decrease in the sulphur content in the soils. Several researches agree on the importance of sulphur as a limiting factor in wheat production and quality deterioration (Byers and Bolton, 1979; Effect of Sulphur Fertilization on Grain Quality and Protein Composition of Durum Wheat (Triticum durum Desf.) Wrigley et al, 1984;Castle and Randall, 1987;MacRitchie and Gupta, 1993;Zhao et al, 1999aZhao et al, , 1999bLuo et al, 2000;Wooding et al, 2000aWooding et al, , 2000bWieser et al, 2004;Lerner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%